2012
DOI: 10.1002/chem.201103131
|View full text |Cite
|
Sign up to set email alerts
|

Hetero‐oligophenylene‐Based AIEE Material as a Multiple Probe for Biomolecules and Metal Ions to Construct Logic Circuits: Application in Bioelectronics and Chemionics

Abstract: New hetero-oligophenylene derivative (2) was synthesized which exhibits aggregation-induced emission enhancement (AIEE) in H(2)O/THF (80:20). The aggregates serve as a biological probe for three different proteins, that is bovine serum albumin (BSA), cytochrome c, and lysozyme, and DNA in contrasting modes. Further, among 29 metal ions tested, the contrasting fluorescence behavior of aggregates of 2 is observed with only Pb(2+) and Pd(2+) ions. Multiple output logic circuits based upon the fluorescence behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…In recent times, a number of organic luminogens display feeble emission in dilute solutions and become strong emissive in aggregated/solid‐state 20 . Molecule demonstrating fluorescence in aggregate or solid state has enormous application in opto‐electronic gadget like OLED and in cutting edge innovation 21–24 . Side by side, AIE phenomenon is a ready and enormous applied technique for nitroexplosive detection via fluorescence quenching 25,26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, a number of organic luminogens display feeble emission in dilute solutions and become strong emissive in aggregated/solid‐state 20 . Molecule demonstrating fluorescence in aggregate or solid state has enormous application in opto‐electronic gadget like OLED and in cutting edge innovation 21–24 . Side by side, AIE phenomenon is a ready and enormous applied technique for nitroexplosive detection via fluorescence quenching 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…20 Molecule demonstrating fluorescence in aggregate or solid state has enormous application in opto-electronic gadget like OLED and in cutting edge innovation. [21][22][23][24] Side by side, AIE phenomenon is a ready and enormous applied technique for nitroexplosive detection via fluorescence quenching. 25,26 In this connection, number of reports in literature on AIE property of salen based Schiff base.…”
mentioning
confidence: 99%
“…Bhalla et al, reported in 2012 synthesizing N-doped, hetero-oligophenylene via DA cycloaddition with CO extrusion involving 1,2-bis(3-pyridyl)acetylene and suitable cyclopentadienone derivative ( Scheme 93 ) [ 147 ].…”
Section: Cyclopentadienones For the Multisubstituted Benzene Ring And Naphthalene System Formationmentioning
confidence: 99%
“…For the real time applications of these materials, the detection of analytes in aqueous media is important, thus, water compatiability of the organic building block is essential. In this context, in 2012, we reported the synthesis of hetero‐oligophenylene derivative 1 by applying the principles of AIE phenomenon [16] . Derivative 1 is a fully aromatic system prepared by covalently linking pyridyl/phenyl groups to the aromatic stator.…”
Section: Development Of Aie‐active Supramolecular Assemblies and Theimentioning
confidence: 99%